2009
DOI: 10.1002/dmrr.954
|View full text |Cite
|
Sign up to set email alerts
|

Serum high‐molecular weight adiponectin is related to early postprandial glycemic increases and gastric emptying in patients with type 2 diabetes mellitus

Abstract: Early postprandial glycemic increases were related to elevated serum high-molecular weight adiponectin, which might be associated with enhanced gastric emptying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
7
1
Order By: Relevance
“…Given the assumption that HM composition potentially influences GE [ 14 , 71 ], in term infants we expected the appetite hormones to be associated with infant GE rate such that high concentrations and/or doses of leptin would result in slower GE [ 30 ], whereas adiponectin might induce faster GE [ 37 ] consistent with both animal and human models. However, neither the concentrations nor doses of these hormones were related to GE rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the assumption that HM composition potentially influences GE [ 14 , 71 ], in term infants we expected the appetite hormones to be associated with infant GE rate such that high concentrations and/or doses of leptin would result in slower GE [ 30 ], whereas adiponectin might induce faster GE [ 37 ] consistent with both animal and human models. However, neither the concentrations nor doses of these hormones were related to GE rate.…”
Section: Discussionmentioning
confidence: 99%
“…In the animal model adiponectin inhibits tension-sensitive gastric vagal afferent mechanosensitivity, modulating satiety signals in both lean and obese animals, while simultaneously increasing the mechanosensitivity of mucosal gastric vagal afferent in the obesity-induced model [ 36 ]. In humans, elevated serum levels of adiponectin are associated with more rapid GE in diabetic patients [ 37 ]. It is not known whether adiponectin levels impact GE in the infant and this warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In another study investigating the role of adiponectin in the early rise in the postprandial glycemic response, Iwase et al . showed that delayed gastric emptying was associated with lower high-molecular weight (HMW) adiponectin, but not total adiponectin [ 35 ]. Although HMW adiponectin was not measured in the present study, further studies with a HMW adiponectin assay may help to clarify the pathophysiology of GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin in human serum forms a wide range of multimers from trimers and hexamers (low and/or medium molecular weight, LMW/MMW) to high molecular weight (HMW) dodecamers and 18 mers. Almost all adiponectin in plasma appears to exist as full-length adiponectin molecule 5961. Recent research has indicated that HMW adiponectin has bioactivity.…”
Section: Plasma Protein Levels and Disease Relationships For Adiponectinmentioning
confidence: 99%
“…Recent research has indicated that HMW adiponectin has bioactivity. Serum HMW adiponectin is related to early postprandial glycemic increases and gastric emptying in T2D patients 61,62. However, a comparative evaluation study with the limited number of subjects (n = 60) does not support the superiority of HMW over total adiponectin in assessing metabolic variables at baseline or in response to physical training 63.…”
Section: Plasma Protein Levels and Disease Relationships For Adiponectinmentioning
confidence: 99%